2009
DOI: 10.1111/j.1872-034x.2009.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Bead‐based microarray analysis of microRNA expression in hepatocellular carcinoma: miR‐338 is downregulated

Abstract: Aim: Recent studies have underlined causative links between microRNA (miRNA) deregulation and cancer development. However, the relevance of abnormally expressed miRNA to tumor biology has not been well understood in hepatocellular carcinoma (HCC).Methods: A bead-based miRNA expression profiling method was performed on 20 pairs of surgically removed HCC and adjacent non-tumorous tissue (NT). Special miR-338 downregulations and miR-338 associated with clinical characteristics was validated in an extended samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 44 publications
11
93
1
Order By: Relevance
“…Relationship between clinicopathological features and miR-107 expression in gastric cancer tissues. Many studies have demonstrated overexpression of miR-107 in gastric, esophageal, colon, hepatocellular and pancreatic cancers, suggesting that this miRNA has some positive role in the carcinogenesis of these cancers (10)(11)(12)(13)(14)(15)(16). It has been reported that miR-107 is an oncogenic miRNA that regulates tumor invasion and metastasis in gastric cancer (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship between clinicopathological features and miR-107 expression in gastric cancer tissues. Many studies have demonstrated overexpression of miR-107 in gastric, esophageal, colon, hepatocellular and pancreatic cancers, suggesting that this miRNA has some positive role in the carcinogenesis of these cancers (10)(11)(12)(13)(14)(15)(16). It has been reported that miR-107 is an oncogenic miRNA that regulates tumor invasion and metastasis in gastric cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that various miRNAs can function as oncogenes or tumor-suppressor genes and play a central role in carcinogenesis (5). Accumulating evidence shows that miR-107 is one of the oncogenic RNAs, and overexpression of these RNAs has been reported in several types of human malignant solid tumors, including gastric, esophageal, pancreatic and colorectal cancer (10)(11)(12)(13)(14)(15)(16). Moreover, miR-107 may contribute to the regulation of the cell cycle in non-small cell lung cancer cell lines (17).…”
Section: Introductionmentioning
confidence: 99%
“…The earlier studies proved that miR-338-3p is downregulated in hepatocellular carcinoma (12) and malignant melanoma (13). In addition, miR-338-3p could suppress progression of cancer cells by targeting smoothened in both liver cancer (14) and colorectal carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…Tsuchiya et al [16] have reported that miR-338-3p contributes to the formation of epithelial basolateral polarity by facilitating the translocalization of β1-integrin to the basolateral membrane, which highlights a potentially important role for miR-338-3p in the process of epithelial cell differentiation. Huang et al [17] demonstrated that a decrease of miR-338-3p expression in hepatocellular carcinoma (HCC), which is another type of epithelial cell-derived cancer, was significantly associated with TNM stage, vascular invasion, intrahepatic metastasis, tumor size and tumor grade. In our previous study, we demonstrated that miR-338-3p expression was down-regulated in both CRC samples and CRC-derived cell lines.…”
Section: Biological Functions Of Mir-338-3p In a Crc-derived Cell Linementioning
confidence: 99%